Haemophilia Experiences, Results and Opportunities (HERO) Study: Influence of haemophilia on interpersonal relationships as reported by adults with haemophilia and parents of children with haemophilia. (7th May 2014) - Cassis, F. R. M. Y.; Buzzi, A.; Forsyth, A.; Gregory, M.; Nugent, D.; Garrido, C.; Pilgaard, T.; Cooper, D. L.; Iorio, A.
Summary Evidence delineating the effects of haemophilia on interpersonal relationships is sparse and largely outdated, failing to reflect the impact of current treatment strategies. HERO (Haemophilia Experiences, Results and Opportunities) was commenced to garner a more comprehensive understanding of psychosocial issues facing persons with haemophilia (PWH). This article describes the findings of the quantitative HERO survey relating to the influence of haemophilia on interpersonal relationships of adult PWH, and parents/caregivers of children with haemophilia. Separate questionnaires were completed by adult PWH and parents of minor children from 10 countries, including satisfaction with support from partners, family, friends and other social contacts; disclosure of haemophilia and carrier status and family dynamics. A total of 675 PWH and 561 parents completed the survey. Over half of PWH (57%) and parents (84%) were married. Most PWH were satisfied with support from partners (94%), family (90%) and friends (85%), with lower percentages reported among those with inhibitors. Most parents were likewise satisfied with support from partners (88%) and family (83%). Whereas PWH were reticent to disclose their diagnosis beyond family and friends, parents were more likely to share their son's diagnosis, and most were satisfied with the support from their son's peers (74%), teachers (83%) and other adults in supervisory roles (85%). PWH and parents surveyed were satisfied overall with the support they received from partners, family, friends and social contacts. Relationships are affected by haemophilia in various ways, and particularly affected in terms of disease burden, age and social life.